Microvascular complications and their prevalence in newly diagnosed type-2 diabetes mellitus - Manhas, Angli; Gupta, Meenakshi; Manhas, Rameshwar S.; Gupta, Dinesh; Manhas, Gaurav S. (International Journal of Research in Medical Sciences, 2019)
Background: A group of metabolic diseases is ‘diabetes’ which has become a major global concern is characterized by high blood sugar. In the world about 347 million people have diabetes. Untreated long standing hyperglycemia leads to microvascular complications in newly diagnosed DM. The objective of the study was to find out prevalence of microvascular complications in newly diagnosed Type-2 diabetes mellitus. Methods: The present cross-sectional study was conducted over a period of 6 months involved 200 patients who were diagnosed with T2DM having ≤6 months duration was conducted in the out-patient department of medicine and ophthalmology at a tertiary care hospital. Informed consent was taken from all the participants who were willing to participate. Detailed history, clinical examination and relevant investigations were done to diagnose microvascular complications. Results: Maximum number of studied subjects i.e. 54% were seen in age group of 41-50 yrs. Males were 56% whereas females comprised 44%. Total of 52% of subjects were from rural background. Nephropathy was the most common microvascular complication present in 54% patients followed by neuropathy in 30% and retinopathy in 8% (NPDR in 7% and PDR in 1%) of patients. Conclusions: From the present study it has been concluded that nephropathy is the most common microvascular complication in newly diagnosed T2DM followed by neuropathy and retinopathy. Authors recommend that education of high-risk group regarding diabetes and its complications by electronic and print media is required so that they seek medical consultation at the earliest. Screening for diabetes at a younger age in view of lower average age at presentation and high prevalence of microvascular complications.